RANKING FACTORS THAT AFFECT SATISFACTION AND MOTIVATION OF EMPLOYEES USING THE PIPRECIA METHOD - Đukić, Tijana (Journal of process management and new technologies, 2022)
Motivating employees is a crucial factor in the use and development of human resources and their focus on achieving organizational goals, increasing satisfaction, retaining quality people, encouraging creativity, and eliminating all forms of counterproductive behavior. Through a series of activities, managers can increase individual development needs, making the objective situation more demanding. Through the example of the generation we paid attention to, Generation Y (1981 - 2000) is often called Millennials and Generation Z, which enters the labor market as the youngest, after millennials. The task of human resource managers is to make each member feel involved in organizational culture in the right way and to feel valued. Therefore, a multicriteria approach based on the application of PIvot has been applied in this paper Pair-wise Relative Criteria Importance Assessment - PIPRECIA method. A detailed review of the literature defines a list of factors and relevant subfactors evaluated by three Generation Y decision-makers and three Generation Z decision-makers. The obtained results are relevant and authoritative, thus unequivocally confirming the usefulness and applicability of the proposed approach.
Keywords: Motivation; leadership; Generation Y and Z; Multiple-criteria decision-making; PIPRECIA method